Computational analysis of upscaled fibrotic liver multi-lobule flows and metabolism - Coombe, Dennis; Wallace, Cooper; Rezania, Vahid; Tuszynski, Jack A. (My University, 2024)
The modeling of fibrotic effects on fluid flow and metabolism in the liver can be computationally challenging. This paper combines innovative concepts based on fundamental physics to address such issues at the level of the liver functional unit, the lobule, and upscales and extends this to a multi-lobule tissue scale analysis. Fibrosis effects on fluid flow and metabolism are introduced using percolation theory and its consequences are explored for single lobule and multi-lobule patterns, without and with distortion.
Keywords: liver; metabolic processes; computational modeling; fibrosis; lobule; fluid flows